Implementation of Intelligent Traffic Analytic in Digital Traffic Contingency Data Mapping (Indonesian Journal of Police Studies, 2023)
Traffic problems become one of the big problem in Bogor. Among them are traffic accidents whose impact the most to the traffic. This is certainly the duty and responsibility of the National Police to overcome these problems. In seeking solutions to these problems the Indonesian National Police can utilize technological developments to improve the quality of traffic management. This also encourages researchers to find solutions to problems by examining the implementation of a new technology before it is implemented, that is INTAN. By describing the mechanism and how the implementation of INTAN, is expected to find out the cause of the problem. This research will use 1 theory and 6 concepts, namely the theory of planned behavior, the INTAN concept, the concept of the basic components of IT for Road Safety, the concept of organizational climate, the concept of user participation, the concept of digital mapping and the concept of traffic contingency data. Data collection is done through observation, interviews with sources and studies of documents that support research that is complemented by efforts to validate data by means of triangulation. Based on this paper, there are also a number of suggestions from researchers including that the National Police be able to coordinate optimally with other agencies, improve SOP’s as well as leadership appeals to members to support new breakthroughs related to the use of technology in dealing with traffic problems and awareness of the importance of the technology implementation process.
Keywords: Traffic Problems, Information Technology, INTAN, IT for Road Safety